2021
DOI: 10.1101/2021.04.07.438040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic Timescales Across the Basal Ganglia

Abstract: Recent studies have shown that neuronal stability over time can be estimated by the structure of the spike-count autocorrelation of neuronal populations. This estimation, called the intrinsic timescale, has been computed for several cortical areas and can be used to propose a cortical hierarchy reflecting a scale of temporal receptive windows between areas. In this study, we performed an autocorrelation analysis on neuronal populations of three basal ganglia (BG) nuclei, including the striatum and the subthala… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Additional studies have replicated and extended the INT hierarchy, reinforcing the idea that brain regions exhibit unique timescales in their intrinsic activity, which reflect functional specialization in terms of temporal integration (Cavanagh, Wallis, Kennerley, & Hunt, 2016;Cirillo, Fascianelli, Ferrucci, & Genovesio, 2018;Fascianelli, Tsujimoto, Marcos, & Genovesio, 2019;Murray et al, 2014;Ogawa & Komatsu, 2010;Rossi-Pool et al, 2021, Maisson et al, 2021. The concept of INT hierarchy has even been extended to subcortical regions-specifically the basal ganglia (Nougaret, Fascianelli, Ravel, & Genovesio, 2021). Moreover, a large-scale network model, based on anatomical connectivity and the strength of local recurrent connectivity, has been used to successfully reproduce the temporal hierarchy (Chaudhuri, Knoblauch, Gariel, Kennedy, & Wang, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Additional studies have replicated and extended the INT hierarchy, reinforcing the idea that brain regions exhibit unique timescales in their intrinsic activity, which reflect functional specialization in terms of temporal integration (Cavanagh, Wallis, Kennerley, & Hunt, 2016;Cirillo, Fascianelli, Ferrucci, & Genovesio, 2018;Fascianelli, Tsujimoto, Marcos, & Genovesio, 2019;Murray et al, 2014;Ogawa & Komatsu, 2010;Rossi-Pool et al, 2021, Maisson et al, 2021. The concept of INT hierarchy has even been extended to subcortical regions-specifically the basal ganglia (Nougaret, Fascianelli, Ravel, & Genovesio, 2021). Moreover, a large-scale network model, based on anatomical connectivity and the strength of local recurrent connectivity, has been used to successfully reproduce the temporal hierarchy (Chaudhuri, Knoblauch, Gariel, Kennedy, & Wang, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…(E) INTs across the MPFC reported by Maisson et al (2021). (F) INTs across the basal ganglia reported by Nougaret et al (2021). The cortical areas were defined separately for each panel to match the recording sites of the data set.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we demonstrated that INTs are organized along spatial gradients that closely matched FC gradients. Nougaret et al (2021). The cortical areas were defined separately for each panel to match the recording sites of the data set.…”
Section: Int Hierarchies Are Closely Related To Fc Gradients Across the Brainmentioning
confidence: 99%
See 2 more Smart Citations